(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
In this article, a comparative analysis of the lexical units of the children’s folklore of Uzbek and English languages is carried out. Children’s nursery rhymes are primarily seen as language values, a tool that reflects national mentality and culture. During the study, the lexical composition of both children’s songs in both languages, images, rhetorical methods and emotional conditions were studied. Traditional words, archaisms, and aesthetic functions of the nursery rhymes are used. The features of the phonetic units and memorizing the lexical units used in these songs also explain the importance of language teaching. Based on a comparative analysis, both languages were identified and the linguocultural bases of these cases explained.